(untitled) (The Pakistan Development Review, 2001)
The present paper consists of four parts. First, it is argued why the Quaid-i- Azam, Mohammad Ali Jinnah (1876-1948), concentrated for the most part on political issues and political freedom, why he went in for Islam as the cultural metaphor in arguing the case for Pakistan, and why he opted for couching his marathon (1937-47) discourse in Islamic terms. Second, the legacy in terms of the primacy of economic factors in propelling a colonised people towards political emancipation Jinnah had received from the historic realm and his own background— in particular, the economic bias in his family background, in Bombay’s mercantile culture which was almost at the centre of the most formative influences in his early life, and in the pronouncements of, and proposals mooted by, Muslim leaders from Sir Syed Ahmad Khan (1817-1898) down to Iqbal (1877-1938) on the one hand, and by the Mohammedan Educational Conference (f.1836) to the All India Muslim League (1906-47), on the other. These proposals were essentially aimed at exhorting the intelligentsia to work for the social, economic and political uplift of the masses. Third, the stress on economic emancipation and the rise of Muslim economic nationalism in the 1940s, in the wake of the Lahore Resolution (1940), has been discussed and delineated briefly.